2018
DOI: 10.1016/j.jadohealth.2017.11.303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Community Pharmacy Responses About Levonorgestrel Emergency Contraception by Mystery Caller Characteristics

Abstract: Persistent barriers to accessing EC exist for adolescents despite regulatory changes to make EC available over-the-counter, especially for females. Additional work to remove these barriers is needed to assure timely access for those who require effective pregnancy prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…Wilkinson's findings are similar to previous work by their group and others [2À10]. Findings from these mystery caller studies showed commonly that access was encouragingly high [1,3,5,7] but that pharmacy advice was not always accurate regarding product use or adverse effects [1,3,5,8,9]. Most importantly, many studies conducted after the 2014 legislative changes found misinformation was given about age restrictions [1,3,5,8À10].…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Wilkinson's findings are similar to previous work by their group and others [2À10]. Findings from these mystery caller studies showed commonly that access was encouragingly high [1,3,5,7] but that pharmacy advice was not always accurate regarding product use or adverse effects [1,3,5,8,9]. Most importantly, many studies conducted after the 2014 legislative changes found misinformation was given about age restrictions [1,3,5,8À10].…”
supporting
confidence: 76%
“…Since 2014, U.S. federal legislative changes allow young people of all ages to access levonorgestrel emergency contraception (EC) without prescription in licensed retail pharmacies. In this issue of the Journal, Wilkinson et al report a mystery caller study across five U.S. states exploring community pharmacy-mediated access to EC [1]. Wilkinson's findings are similar to previous work by their group and others [2À10].…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Availability of LNG EC in pharmacies across the U.S. has been demonstrated in many studies over the years. Due to the many change to LNG EC access over the years, the most relevant studies are those in the last few years that found 80–83% same-day availability of LNG EC, compared to 90% in this study [13,14,15].…”
Section: Discussionmentioning
confidence: 56%
“…The SmPCs do not specify age limits, but the BAK guidelines recommend not to dispense EC to girls under 14 without a prescription or the consent of a parent or legal guardian [9,32]. However, it remains arguable if the overall restrictive EC dispensing due to pharmacists' concerns about the safe use of EC may constitutes an (unnecessary) barrier for women who require early and effective pregnancy prevention [33]. As indicated, EC have an adequate safety profile, and the benefit outweigh the risk [34][35][36].…”
Section: Discussionmentioning
confidence: 99%